Feedforward neural control of toe walking in humans. (15th April 2018) - Lorentzen, Jakob; Willerslev‐Olsen, Maria; Hüche Larsen, Helle; Svane, Christian; Forman, Christian; Frisk, Rasmus; Farmer, Simon Francis; Kersting, Uwe; Nielsen, Jens Bo
Abstract : Key points: Activation of ankle muscles at ground contact during toe walking is unaltered when sensory feedback is blocked or the ground is suddenly dropped. Responses in the soleus muscle to transcranial magnetic stimulation, but not peripheral nerve stimulation, are facilitated at ground contact during toe walking. We argue that toe walking is supported by feedforward control at ground contact. Abstract: Toe walking requires careful control of the ankle muscles in order to absorb the impact of ground contact and maintain a stable position of the joint. The present study aimed to clarify the peripheral and central neural mechanisms involved. Fifteen healthy adults walked on a treadmill (3.0 km h −1 ). Tibialis anterior (TA) and soleus (Sol) EMG, knee and ankle joint angles, and gastrocnemius–soleus muscle fascicle lengths were recorded. Peripheral and central contributions to the EMG activity were assessed by afferent blockade, H‐reflex testing, transcranial magnetic brain stimulation (TMS) and sudden unloading of the planter flexor muscle–tendon complex. Sol EMG activity started prior to ground contact and remained high throughout stance. TA EMG activity, which is normally seen around ground contact during heel strike walking, was absent. Although stretch of the Achilles tendon–muscle complex was observed after ground contact, this was not associated with lengthening of the ankle plantar flexor muscle fascicles. Sol EMG around ground contact was not affected by ischaemic blockade of large‐diameter sensory afferents, or the sudden removal of ground support shortly after toe contact. Soleus motor‐evoked potentials elicited by TMS were facilitated immediately after ground contact, whereas Sol H‐reflexes were not. These findings indicate that at the crucial time of ankle stabilization following ground contact, toe walking is governed by centrally mediated motor drive rather than sensory driven reflex mechanisms. These findings have implications for our understanding of the control of human gait during voluntary toe walking. Key points: Activation of ankle muscles at ground contact during toe walking is unaltered when sensory feedback is blocked or the ground is suddenly dropped. Responses in the soleus muscle to transcranial magnetic stimulation, but not peripheral nerve stimulation, are facilitated at ground contact during toe walking. We argue that toe walking is supported by feedforward control at ground contact.